2022
DOI: 10.1007/s00170-022-08885-y
|View full text |Cite
|
Sign up to set email alerts
|

Development and implementation of crater and flank tool wear model for hard turning simulations

Abstract: This paper concerns the tool wear in hard turning of AISI 52100 hardened steel by means of PCBN tools. The purposes of this work are the development of a tool wear model and its implementation in a FEM-based procedure for predicting crater and flank wear progression during machining operations for studying the influence of tool wear on the process in terms of tool geometry modifications and stress variation on the tool. The developed tool wear model, able to update the geometry of the worn tool as a function o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The flank wear value, accepted as a criterion for evaluating the cutting tool life, can provide information, especially about the material's machinability. According to the ISO 3685:1993 tool life test standard [49], for a tool to complete its life, it must reach an average flank wear value of 0.3 mm, a maximum flank wear value of 0.6 mm, or a severe tool failure criterion [40,50,51].…”
Section: Maximum Flank Wearmentioning
confidence: 99%
“…The flank wear value, accepted as a criterion for evaluating the cutting tool life, can provide information, especially about the material's machinability. According to the ISO 3685:1993 tool life test standard [49], for a tool to complete its life, it must reach an average flank wear value of 0.3 mm, a maximum flank wear value of 0.6 mm, or a severe tool failure criterion [40,50,51].…”
Section: Maximum Flank Wearmentioning
confidence: 99%
“…Therefore, the Finite Element Method (FEM) of machining processes has received much attention by numerous researchers in the last decades [3]. This method was successfully implemented to improve the understanding of crater and flank tool wear in turning [4] and determination of residual stresses [5] or interactions in the chip forming process with internal lubrication in sawing [6]. The underlying idea of FEM is the discretization of the tool and the workpiece and employing a stiffness structure [7].…”
Section: Introductionmentioning
confidence: 99%
“…They found that turning speed has the main impact on tool wear, and turning depth has the least impact on tool wear. Cappellini C et al [8] and Suresh R et al [9] conducted a study on tool life prediction in hard turning.…”
Section: Introductionmentioning
confidence: 99%